Active Learning of Arabic Language at High School in Jombang - M Dzikrul Hakim Al Ghozali; Mustamim Mustamim (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Active learning is learning that focuses on students in every learning process. The purpose of this study is to describe active Arabic learning at five madrasah/high schools in Jombang. The research approach used is a qualitative approach. Data related to active learning patterns were obtained by interviewing Arabic teachers at five madrasas/schools. Furthermore, the collected data were analyzed using a qualitative descriptive analysis method with the steps of data reduction, data display, and drawing conclusions/verification. this study concludes that: First, identification of Arabic language elements is the most urgent thing for trainers, teachers and learners in the process of learning Arabic. Second, the practice of active learning Arabic in five madrasas/schools has different learning patterns or is not patent. Third, the active learning patterns used include drill, role playing, study groups, self learning, mudzakarah.